2021
DOI: 10.3126/forestry.v18i01.41757
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of carbon stocks in the Sal forest (Shorea robusta) in core and buffer zones of Shuklaphanta National Park, Nepal

Abstract: Forests play a significant role in sequestering carbon and regulating the global carbon and energy cycles. The amount of carbon in different carbon pools also varies at regional to local scales depending upon the environmental factors and forest management practices. This study was carried out to quantify and compare the carbon stocks in the Sal (S. robusta) forest in the core and buffer zones of Shuklaphanta National Park in Kanchanpur district of Nepal. A total of 50 sample plots with 25 in each core and buf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The thinning, pruning, clearance of leaf litter, cutting, and logging of the trees for the livelihood sustainability of the local people, as well as the disturbance from cattle grazing inside the CF, may have led to the lower carbon stock. Our finding is consistent with some studies in Nepal [9,34,35], where the total carbon stock in the undis-…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The thinning, pruning, clearance of leaf litter, cutting, and logging of the trees for the livelihood sustainability of the local people, as well as the disturbance from cattle grazing inside the CF, may have led to the lower carbon stock. Our finding is consistent with some studies in Nepal [9,34,35], where the total carbon stock in the undis-…”
Section: Discussionsupporting
confidence: 94%
“…The thinning, pruning, clearance of leaf litter, cutting, and logging of the trees for the livelihood sustainability of the local people, as well as the disturbance from cattle grazing inside the CF, may have led to the lower carbon stock. Our finding is consistent with some studies in Nepal [9,34,35], where the total carbon stock in the undisturbed forest (where human interference is limited) was higher than that of the disturbed forest (human interference is allowed). However, our estimated total carbon stock in both the management approaches was much lower than in other studies [6,7,36,37].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The aboveground carbon stock recorded in Shorea robusta forest was found higher than the other Shorea robusta forest of Terai region of Nepal. Other studies conducted in Shorea robusta forest reported 129.53-162.98 Mg ha -1 (Bhatta et al, 2021), 74.64±16.34 -163.12±20.23 t ha (Joshi et al, 2020) 1 and 160.4 Mg ha -1 (Regmi et al, 2021) in Nepal and 72.32 -143.36 t ha− 1 (Raj & Jhariya, 2021)in India. However, it is markedly…”
Section: Discussionmentioning
confidence: 85%
“…Higher SOC in the managed CF was a result of the prevention of forest fires and livestock grazing. The presence of decomposable organic matter from branches and litter fall can boost the soil carbon in forests (Jati, 2012;Bhatta et al, 2021). Such boosting can occur significantly in the managed forest.…”
Section: Discussionmentioning
confidence: 99%